(untitled) - Wetzstein, Michael E. (Victoria, Australia, 2005)
This book is a calculus-based microeconomic theory text for undergraduates and graduates that successfully balances theoretical/intuitive (verbal), graphical (visual), and mathematical presentation in order to appeal to various learning styles. The text combines theory and applications more completely than most offerings in this course area, and bridges the gap between low-level texts that relegate math to footnotes and upper-level texts that focus only on math at the expense of theory and applications.
Keywords: Microeconomics